2018
DOI: 10.1115/1.4039352
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Analytical Solution of the Heat Transfer Including Viscous Dissipation in the Steady Flow of a Sisko Fluid in Cylindrical Tubes

Abstract: Hydrodynamically and thermally fully developed flow of a Sisko fluid through a cylindrical tube has been investigated considering the effect of viscous dissipation. The effect of the convective term in the energy equation has been taken into account, which was neglected in the earlier studies for Sisko fluid flow. This convective term can significantly affect the temperature distribution if the radius of the tube is relatively large. The equations governing the flow and heat transfer are solved by the least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…It is evident from the figure that Nu decreases with an increase in Br. The same trend is also reported in the literature for flow of Newtonian fluids through pipes 41,58 . An increase in Br indicates higher viscous dissipation, resulting in an increase in temperature of the flowing fluid.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…It is evident from the figure that Nu decreases with an increase in Br. The same trend is also reported in the literature for flow of Newtonian fluids through pipes 41,58 . An increase in Br indicates higher viscous dissipation, resulting in an increase in temperature of the flowing fluid.…”
Section: Resultssupporting
confidence: 87%
“…These fluids show a variety of different characteristics, such as shear thinning/thickening and elastic behavior, which are not shown by Newtonian fluids. Various rheological models 37‐40 are in use for such types of fluids, but third grade fluid (TGF) model is widely used to handle such types of fluids due to its ability to correctly capture various non‐Newtonian effects 41 . In the present work, a TGF flow problem is solved by a semianalytical method: least square method (LSM) 42,43 .…”
Section: Introductionmentioning
confidence: 99%
“…Some more recent analysis expressing the rheological mechanism of non-Newtonian materials can be shown in Refs. [6][7][8][9][10] The nano-materials are the materials that contain particles in the size range of 1-100 nm. A lot of research has been done on the properties and studies of nano materials in the last few years because of their wide range of applications in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…Some more recent analysis expressing the rheological mechanism of non-Newtonian materials can be shown in Refs. 610…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the effect of viscous dissipation could not be neglected when the wall temperature was uniform. For in-tube thermal conditions, Chaudhuri and Das [6] by using semi-analytical method, Teleszewski [7] for a tube with adiabatic wall and Newtonian fluid, Daghighi and Norouzi [8], and Dang [9] for a constant temperature wall condition, have been studied the effect of viscous dissipation in the thermal input region of a tube.…”
Section: Introductionmentioning
confidence: 99%